2000
DOI: 10.1002/(sici)1097-0193(200005)10:1<16::aid-hbm30>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation in the processing of Chinese characters and words: A functional MRI study

Abstract: Functional magnetic resonance imaging was used to identify the neural correlates of Chinese character and word reading. The Chinese stimuli were presented visually, one at a time. Subjects covertly generated a word that was semantically related to each stimulus. Three sorts of Chinese items were used: single characters having precise meanings, single characters having vague meanings, and two-character Chinese words. The results indicated that reading Chinese is characterized by extensive activity of the neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 26 publications
10
53
1
Order By: Relevance
“…In short, Chinese character recognition has been shown to involve less LH processing/ more RH processing compared with word recognition in alphabetic languages, in particular in the orthographic/visual word form processing. Consistent with the behavioral data, although most of the existing fMRI studies on Chinese character recognition usually used character pronunciation or semantic tasks, they generally showed more RH-lateralized activation relative to English reading particularly in the visual areas (e.g., Tan et al, 2000Tan et al, , 2001. Although in contrast to Chinese character recognition, the recognition of Chinese two-character words has been shown to have a RVF/LH advantage in tachitoscopic word identification tasks (e.g., Tzeng et al, 1979;Cheng & Yang, 1989;note, however, that Keung & Hoosain, 1989; reported a RH advantage in processing high stroke number low frequency two-character Chinese words with short exposure time and low luminance), fMRI studies of Chinese word pronunciation also in general showed more bilateral or RH-lateralized activation in the occipitotemporal system, in contrast to the typically LH-lateralized occipitotemporal activation in English word reading (according to a meta-analysis by Tan, Laird, Li, & Fox, 2005; see also Kuo et al, 2001).…”
Section: Introductionsupporting
confidence: 68%
“…In short, Chinese character recognition has been shown to involve less LH processing/ more RH processing compared with word recognition in alphabetic languages, in particular in the orthographic/visual word form processing. Consistent with the behavioral data, although most of the existing fMRI studies on Chinese character recognition usually used character pronunciation or semantic tasks, they generally showed more RH-lateralized activation relative to English reading particularly in the visual areas (e.g., Tan et al, 2000Tan et al, , 2001. Although in contrast to Chinese character recognition, the recognition of Chinese two-character words has been shown to have a RVF/LH advantage in tachitoscopic word identification tasks (e.g., Tzeng et al, 1979;Cheng & Yang, 1989;note, however, that Keung & Hoosain, 1989; reported a RH advantage in processing high stroke number low frequency two-character Chinese words with short exposure time and low luminance), fMRI studies of Chinese word pronunciation also in general showed more bilateral or RH-lateralized activation in the occipitotemporal system, in contrast to the typically LH-lateralized occipitotemporal activation in English word reading (according to a meta-analysis by Tan, Laird, Li, & Fox, 2005; see also Kuo et al, 2001).…”
Section: Introductionsupporting
confidence: 68%
“…It is worth mentioning that previous studies documented the word specificity of N170 in the left hemisphere; we found the sensitivity of N170 to character likeness in both hemispheres, which indicated that the property of character likeness would not modulate the lateralization. One explanation, as mentioned earlier, is that pictographs elicited bilateral activations, which reflected the greater visuospatial analysis, because of years of experience in processing Chinese characters (a script that relies on visuospatial analysis and consequently recruits the right hemisphere; Liu, Dunlap, Fiez, & Perfetti, 2007;Tan, Laird, Li, & Fox, 2005;Tan et al, 2000). Second, the present study found that the latencies of N170, but not P100, were also tuned to character likeness with shorter latencies to more character-like stimuli, although the results were not entirely consistent across the two hemispheres and across the two types of evaluation data of character likeness.…”
Section: Tuning Of N170 To Character Likenessmentioning
confidence: 95%
“…Furthermore, to clearly differentiate between children and adults, studies with adolescents were excluded [e.g., Gr€ unling et al, 2004;Landi et al, 2010]. Several potentially interesting studies could not be included in the meta-analysis because readingrelated activation was not reported separately for young and older readers [Brown et al, 2005;Schlaggar et al, 2002;Turkeltaub et al, 2003], or not in terms of 3-D coordinates in standard stereotactic space on the whole-brain level [e.g., Holland et al, 2001;Shaywitz et al, 2002Shaywitz et al, , 2007, or not for an alphabetic language [Chinese: Cao et al, 2009;Chou et al, 2009;Tan et al, 2000;Siok et al, 2003;or Japanese: Nakamura et al, 2000Miura et al, 2005]. This specific study selection was intended to improve the quality and accuracy of the meta-analytic results.…”
Section: Adultsmentioning
confidence: 99%